PENGEMBANGAN MODUL IPS PADA MATERI GEJALA ALAM DI INDONESIA DENGAN PENDEKATAN SCIENTIFIC BAGI MAHASISWA PGSD - Erviana, Vera Yuli (Universitas Muhammadiyah Surakarta, 2018)
Abstract: This research aims to develop and produce Social Studies module.Â The module leaning material is natural phenomena in Indonesia with scientific approach. The module develops for college-students of Elementary School Teacher Education, Ahmad Dahlan University. This research was a Research and Development. The development of the module is based on Analyze, Design, Development, Implementation and Evaluation (ADDIE). Data collection techniques are interviews, product assessment by experts, and college-students response sheets.Â The instruments of this research are 1) interview guideline to get preliminary information on the analysis of needs in the Elementary School Teacher Education Program; 2) product assessment sheet which is in the form of assessment sheet by expert judgment and expert input in the FGD, and 3)college-students response sheet to understand the module's practicality. The results of the research show the moduleâ€™s feasibility by the material and learning experts with an average score of 120, with